Evaluation of risk factors for diabetic nephropathy among newly diagnosed type 2 diabetic subjects: preliminary report from a tertiary care hospital of Bangladesh (BIRDEM Medical Journal, 2020)
Background: Diabetes mellitus (DM) is the leading cause of chronic kidney disease through-out the world andhalf of the type 2 DM (T2DM) patients remain undiagnosed. During diagnosis, one-third to half of the T2DMpatients may have different macro- and micro-vascular complications including diabetic nephropathy. This studyaimed to evaluate selected risk factors for diabetic nephropathy among newly detected T2DM subjects.Methods: A case-control study was done at out-patient department of BIRDEM General Hospital, Dhaka,Bangladesh from October 2016 to June 2017. Newly detected (